5-Aryl-2-(naphtha-1-yl)sulfonamido-thiazol-4(5H)-ones as clathrin inhibitors. Issue 47 (17th November 2016) - Robertson, Mark J.; Horatscheck, André; Sauer, Samantha; von Kleist, Lisa; Baker, Jennifer R.; Stahlschmidt, Wiebke; Nazaré, Marc; Whiting, Ainslie; Chau, Ngoc; Robinson, Phillip J.; Haucke, Volker; McCluskey, Adam
Abstract : The development of a ( Z )-5-((6, 8-dichloro-4-oxo-4 H -chromen-3-yl)methylene)-2-thioxothiazolidin-4-one (2 ), rhodanine-based lead that led to the Pitstop® 2 family of clathrin inhibitors is described herein. Abstract : The development of a ( Z )-5-((6, 8-dichloro-4-oxo-4 H -chromen-3-yl)methylene)-2-thioxothiazolidin-4-one (2 ), rhodanine-based lead that led to the Pitstop® 2 family of clathrin inhibitors is described herein. Head group substitution and bioisosteric replacement of the rhodanine core with a 2-aminothiazol-4(5 H )-one scaffold eliminated off target dynamin activity. A series of N -substituents gave first phenylglycine (20, IC50 ∼ 20 μM) then phenyl (25, IC50 ∼ 7.1 μM) and 1-napthyl sulfonamide (26, Pitstop® 2 compound, IC50 ∼ 1.9 μM) analogues with good activity, validating this approach. A final library exploring the head group resulted in three analogues displaying either slight improvements or comparable activity (33, 38, and29 with IC50 ∼ 1.4, 1.6 and 1.8 μM respectively) and nine others with IC50 < 10 μM. These results were rationalized using in silico docking studies. Docking studies predicted enhanced Pitstop® 2 family binding, not a loss of binding, within the Pistop® groove of the reported clathrin mutant invalidating recent assumptions of poor selectivity for this family of clathrin inhibitors.